Problematika Kebijakkan Pendidikan di Tengah Pandemi dan Dampaknya Terhadap Proses Pembelajaran di Sekolah Dasar - Syariful Anam; Elya Umi Hanik (Qiro'ah : Jurnal Pendidikan Agama Islam, 2020)
The Covid pandemic has changed the entire order of human life, especially in the world of education. This requires education to change and adapt quickly to continue the learning process. The purpose of this article is to examine the impact of the Ministry of Education and Culture of the Republic of Indonesia policy on Work From Home (WFH) in education, especially among elementary schools. This article was written by reviewing articles and related references about online learning policies that are considered a solution to continue the learning process when schools are closed to avoid spreading the virus. However, on the other hand, this policy has had an impact on the process of transforming knowledge both for students, teachers and parents or families. This study uses a qualitative method based on library research (libraries).